Comparative anatomy of the gut of the South American species of Amitermes, with description of two new species and an identification key based on soldiers and workers - Rocha, Mauricio M.; Cancello, Eliana M. (Zootaxa, 2020)
In this contribution we present updates on the taxonomy and morphology of the South American species of Amitermes. Two new species are described: Amitermes bandeirai, sp. n., from Brazil, and Amitermes lilloi, sp. n., from Argentina. Amitermes nordestinus is a junior synonym of Amitermes aporema. The imago of A. aporema is described for the first time. Detailed comparative gut anatomy of the eight species is presented for the first time. The geographic distribution of Amitermes in South America is expanded and the distribution patterns of some species are discussed.